Analysis Of The Implementation Of Management Information Systems On Bataramas Employee Performance - Sugito, Asep; Fahlevi, Reza; Ridwan, Aditya (JAKI : Jurnal Akuntansi, 2024)
Management information system is a system that is created to make it easier for all parts of the company to get the information they need. Information systems have a big role in changing the company, one of which is improving employee performance with data loaded through the information system. In a company, employee performance will affect how the company develops, it can be fast or slow, this depends on the quality of the company. Batara Mas Company implements various types of information systems, according to the needs required. All activities carried out in the company are collected through the information system to be used as an evaluation and to improve employee performance towards a better direction. Data retrieval will be carried out through the website research journal adjusted to the data needed regarding the analysis of the application of the management information system to the performance of Batara Mas employees.